Recent advances in production of poly(lactic acid) (PLA) nanocomposites: a versatile method to tune crystallization properties of PLA. Issue 2 (29th April 2015) - Murariu, Marius; Dechief, Anne-Laure; Ramy-Ratiarison, Rindra; Paint, Yoann; Raquez, Jean-Marie; Dubois, Philippe
Abstract: A new approach leading to poly(lactic acid) (PLA) nanocomposites designed with improved nucleating/crystallization ability has been developed. As proof of concept, nanofillers of different morphology (organo-modified layered silicates, halloysite nanotubes and silica) were surface-treated with ethylene bis-stearamide (EBS), a selected fatty amide able to promote chain mobility during PLA crystallization from the melt and nucleation. The fine dispersion of the nucleating additive via nanoparticles (NPs) as 'nano-template' is leading to nanocomposites showing unexpected improvements in PLA crystallization rate. This was evidenced by differential scanning calorimetry (DSC) from the high values of the degree of crystallinity (20–40%) with respect to neat PLA (4.3%) and the sharp decrease in crystallization half-time under isothermal conditions (at 110°C), even below one minute. Furthermore, after injection molding the outstanding crystallization properties of PLA were again confirmed. Accordingly, the PLA-nanofiller/EBS nanocomposites revealed remarkable degree of crystallinity (in the range of 30–40%). Surprisingly, the presence of EBS can significantly increase the impact resistance of PLA and PLA based nanocomposites. By considering the remarkable increasing in crystallinity, a key parameter to allow PLA utilization in durable applications, the development of the new approach is expected to lead to significant improvements in the processing and performances of PLA products. Abstract :